Global environmental issues - Harris, Frances (Frances M. A.) (Chichester, West Sussex ; Hoboken, NJ : Wiley-Blackwell, 2012)
Global Environmental Issues, second edition builds on the popularity of the first edition, viewing global environmental problems as complex issues with a network of causes, influenced by a range of actors with differing priorities. The book recognises that science underpins much of what happens in society and therefore it is important to be able to interpret the environmental and social consequences of scientific developments. In addition to discussing the main biophysical causes, the book illustrates how socio-economic and political factors determine why and how people use land, resources and.
9 Sustainable Urbanisation10 Coping with Pollution Dealing with Waste; Part Six Conclusion; 11 Sustainable Development: Negotiating the Future; List of Abbreviations and Acronyms; References; Index.
Includes bibliographical references and index.
Print version record.
Keywords: Environmental monitoring; Environmental policy; Environmental sciences; Environmental protection; Environmental Studies; POLITICAL SCIENCE -- Public Policy -- Environmental Policy; SCIENCE -- Environmental Science; Environmental monitoring; Environmental policy; Environmental sciences; Electronic books